THE ENVIRONMENTAL ASPECTS OF ALEXANDRE DUMAS’S THE COUNT OF MONTE CRISTO - Gusti Ayu Made Rai Suarniti (Ma Chung Press, 2021)
ABSTRACT The topic of this research is about environments that are found in Alexandre Dumas’s The Count of Monte Cristo. This research investigates the environments and their function in the novel. This research utilized the novel entitled The Count of Monte Cristo written by Alexandre Dumas (1997) as the data source. Collection of data were done in a form of library research, which consist of reading the data source and underlining and/or noting the relevant data. All data were classified into their respective kind and function of settings. The collected data were analyzed descriptively. The result of the research showed that four kinds of environments and five functions it were found in Alexandre Dumas’s The Count of Monte Cristo. The four environments found were place, time, social environment, and atmosphere. The five functions found were environment as background for action, environment antagonist, environment a means of creating appropriate atmosphere, environment a means of revealing character, environment as means of reinforcing theme.